PENGARUH PENGGUNAAN TEKNIK MIND MAPPING BERBASIS MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 2 NAN SABARIS - Emidar, Rika Adriyani, Irfani Basri, (Universitas Negeri Padang, 2017)
The purpose of this research are (1) to describe writing ability level on exsposition text on the student SMP Negeri 2 Nan Sabaris grade VIII without using mind mapping technique as a base discovery learning model. (2) to describe writing ability on exsposition text on student SMP Negeri 2 Nan Sabaris grade VIII using mind mapping technique as a base discovery learning model in writing exposition text on the student SMP Negeri 2 Nan Sabaris grade VIII. Based on data analysis, mind mapping technique as a base discovery learning model have effect for writing ability level on exposition text on the student SMP Negeri 2 Nan Sabaris.Kata kunci: pengaruh, teknik mind mapping, model Discovery Learning, dan menulis, teks eksposisiÂ